Bending strategies of convergently evolved, articulated coralline algae. Issue 3 (19th April 2018) - Janot, Kyra G.; Martone, Patrick T.
Abstract : The evolution of uncalcified genicula in upright calcified corallines has occurred at least three times independently, resulting in articulated corallines within Corallinoideae, Lithophylloideae, and Metagoniolithoideae. Genicula confer flexibility to otherwise rigid thalli, and the localization of bending at discrete intervals amplifies bending stress in genicular tissue. Genicular morphology must, therefore, be balanced between maintaining flexibility while mitigating or resisting stress. Genicula in the three articulated lineages differ in both cellular construction and development, which may result in different constraints on morphology. By studying the interaction between flexibility and morphological variation in multiple species, we investigate whether representatives of convergently evolving clades follow similar strategies to generate mechanically successful articulated fronds. By using computational models to explore different bending strategies, we show that there are multiple ways to generate flexibility in upright corallines but not all morphological strategies are mechanically equivalent. Corallinoids have many joints, lithophylloids have pliant joints, and metagoniolithoids have longer joints—while these strategies can lead to comparable thallus flexibility, they also lead to different levels of stress amplification in bending. Moreover, genicula at greatest risk of stress amplification are typically the strongest, universally mitigating the trade‐off between flexibility and stress reduction.